Comparison of three school feeding strategies for primary school children in an informal settlement in Gauteng, South Africa - Carin Napier; Wilna Oldewage-Theron; Jeanette Kearney (AOSIS, 2009)
The aim of this study was to compare the impact of three school feeding strategies on the nutritional status of primary school children aged six to 13 in an informal settlement in Gauteng. The methods included dietary surveys and anthropometric and biochemical measurements of a sample of 160 primary school children allocated to three different school feeding intervention groups. One group (n=60) received a whole wheat pilchard and spinach vetkoek, a second received food according to the Government Primary School Nutrition Programme (PSNP)(n=60), and a third (n=40) received fruit. The children were given these items every day for seven months, except during school holidays and weekends. The baseline anthropometric measurements indicated that 13.6%, 20.9% and 10.8% of the children in the vetkoek, PSNP and fruit groups respectively were underweight (lesser than 5th percentile for weight-for-age) and 17.3%, 23.6% and 5.2% were stunted (lesser than 5th percentile for height-for-age). The post-intervention results indicated that the children in all three groups had improved significantly in weight and height, and in dietary intakes of zinc and iron. The results of this study indicated that all three feeding strategies contributed to an improved nutritional status. Providing fruit as a school feeding strategy may be the most affordable and easy to implement. More research is recommended to measure the impact of these strategies on a long- term basis. Opsomming Die doel van die studie was om die impak van drie skoolvoedingstrategieë op die voedingstatus van ses tot dertien jaar oue laerskoolkinders in 'n informele nedersetting in Gauteng te bepaal. Die metodes het die volgende ingesluit: dieetopnames, antropometriese en biochemiese metings in 'n steekproef van 160 laerskoolkinders, wat ewekansig in drie skoolvoedingintervensiegroepe verdeel is. Die groepe het bestaan uit 'n volkoring sardyn-en-spinasie-vetkoek groep (n=60), die Government Primary School Nutrition Programme (PSNP) groep (n=60), en 'n vrugtegroep (n=40) wat hierdie items elke dag vir sewe maande, behalwe vir skoolvakansies en naweke, ontvang het. Die antropometriese metings voor die intervensie het bevind dat 13.6%, 20.9% en 10.8% van die kinders ondergewig (kleiner as 5de persentiel vir gewig-vir-ouderdom) was in die vetkoek-, PSNP- en vrugtegroep, respektiewelik, en 17.3%, 23.6% en 5.2% se groei is belemmer (kleiner as 5de persentiel vir lengte-vir-ouderdom). Die na-intervensieresultate het aangedui dat die kinders in al drie die groepe se gewig, lengte, sowel as sink en ysterinname betekenisvol verbeter het. Die resultate van hierdie studie het aangetoon dat al drie die voedingstrategieë bygedra het tot 'n verbeterde voedingstatus. Die voorsiening van vrugte as 'n skoolvoedingstrategie is egter bekostigbaar en maklik om te implementeer. Meer navorsing om die impak op die langtermyn te toets, word aanbeveel.